Food security as a pillar of regional resilience: A study of social resilience among coastal and agricultural communities to stunting in Majene - Muhammad Sajidin; Adli Putra Ernanda; Muhammad Sulthan; Mu’min Mu’min (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the role of food security as a pillar of regional resilience by examining the social resilience of coastal and agricultural communities in addressing stunting problems in Majene Regency. Food security is not only understood as food availability, but also as a key foundation for human development and regional resilience, particularly in geographically and socioeconomically vulnerable areas. The research involved two main communities: fishermen groups in Tamo Village representing coastal communities, and farmer groups in Pamboborang Village representing agricultural communities. This study employed a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and local document analysis. The findings reveal that social resilience—reflected in mutual cooperation, local food management, and crisis adaptation—significantly contributes to strengthening household food security and reducing the risk of stunting in children. However, challenges persist, including limited access to nutritious food, lack of health education, and inadequate institutional support. This study confirms that community-based food security can serve as an effective strategy to enhance regional resilience. Therefore, policy interventions that integrate social, economic, and cultural approaches are urgently needed to strengthen food security systems and reduce the prevalence of stunting in coastal and agricultural areas of Majene Regency.